Slinging the Bling - Dent, Grace (London Hodder Children's Books, 2007)
Keeping a diary isn't exactly cool but Shiraz Bailey Wood (15) knows she'd best start writing one. She's going to need it in a few years when she writes her best-selling autobiography.
Keywords: High school seniors -- Manners and customs -- Manners and customs